Puzzle question... I know how to solve it, and will post my solution if needed; but those who wish may participate in the spirit of coming up with elegant solutions rather than trying to teach me how to solve it. [paraphrased from Lone Learner]

Evaluate the continued fraction $$ 1+\cfrac{-5}{13+\cfrac{-128}{37+\cfrac{-693}{73+\cfrac{-2240}{121+\ddots}}}}= b_0+\cfrac{a_1}{b_1+\cfrac{a_2}{b_2+\cfrac{a_3}{b_3+\cfrac{a_4}{b_4+\ddots}}}} $$ where $b_n = 6n^2+6n+1$, $a_n=4n^2-9n^4$.

Can you determine whether it converges, and if so find its value? Numerical computations suggest it converges extremely slowly.


We want to apply the generating-function method with Hayman's method to determine asymptotics of the coefficients, as in LINK.

Let $$\begin{align*} p_n &= (6n^2+6n+1) p_{n-1}+(4n^2-9n^4) p_{n-2}, \quad p_{-1} = 1, \quad p_0=1, \\ q_n &= (6n^2+6n+1) q_{n-1}+(4n^2-9n^4)q_{n-2}, \quad q_{-1} = 0, \quad q_0=1, \\ r_n &= \frac{p_n}{q_n}. \end{align*}$$ So the $r_n$ are the convergents of the continued fraction: $$ r_0 = 1,\quad r_1 = 1+\cfrac{-5}{13},\quad r_2 = 1+\cfrac{-5}{13+\cfrac{-128}{37}},\quad r_3 = 1+\cfrac{-5}{13+\cfrac{-128}{37+\cfrac{-693}{73}}}, $$

Now a problem is that generating functions $$ \sum_{n=0}^\infty p_n x^n,\qquad\text{and}\qquad \sum_{n=0}^\infty p_n \frac{x^n}{n!} $$ both have radius of convergence zero. So they are no good in Hayman's method. So we will use "Bessel" generating functions $$ f(x) = \sum_{n=0}^\infty p_{n-1}\frac{x^n}{(n!)^2},\qquad g(x) = \sum_{n=0}^\infty q_{n-1}\frac{x^n}{(n!)^2} . $$

Use the recurrences to compute the differential equations these satisfy. They are $$\begin{align*} L[f]&=0,\qquad f(0)=1,\qquad f'(0)=1, \tag{1} \\ L[g]&=1,\qquad g(0)=0,\qquad g'(0)=1, \tag{2} \end{align*}$$ where second-order linear differential operator $L$ is given by $$ L[\phi](x) = x(1-3x)^2 \phi''(x)+(1-3x)(1-9x)\phi'(x)+(-1+5x)\phi(x) $$ Now the solution of (1) is $$ f(x) = (1-3x)^{-1/3} = 1 + x + 2 x^2 + \frac{14}{3} x^3 + \frac{35}{3} x^4 +O(x^5) . $$ The coefficient shows $$ p_{n-1} \sim \frac{(n!)^2 3^n n^{-2/3}}{\Gamma(1/3)} $$ With the help of Maple, I get the solution of (2) as $$ g(x) = \frac{3}{2}(1-3x)^{-2/3} + \sqrt{3}\arctan\left(\frac{1+2(1-3x)^{1/3}}{\sqrt{3}}\right)(1-3x)^{-1/3}- \frac{9+2\pi\sqrt{3}}{6}(1-3x)^{-1/3} $$ and in powers of $(1-3x)$, $$ g(x) = \frac{3}{2}(1-3x)^{-2/3}- \left(\frac{\pi}{2\sqrt{3}}+\frac{3}{2}\right)(1-3x)^{-1/3}+\frac{3}{2}+ O\left((1-3x)^{1/3}\right) . $$ Now we need to examine the coefficients at $x=0$ for the Taylor series. The first term has coefficient given asymptotically by $C 3^n n^{-1/3}$. The second term by $C 3^n n^{-2/3}$, the constant term by $0$. So overall we get $$ q_{n-1} \sim C (n!)^2 3^n n^{-1/3} . $$ So the convergent $$ r_{n-1} = \frac{p_{n-1}}{q_{n-1}} \sim C n^{-2/3+1/3} $$ goes to zero. The value of the continued fraction is $0$.

Note that the differential operator $L$ in terms of $y=1-3x$ is $$ 9y^2(1-y)\phi''(x)+9y(2-3y)\phi'(y)+(2-5y)\phi(y) $$ with indicial polynomial $9r(r-1)+18r+2 = (3r+2)(3r+1)$ roots $-1/3, -2/3$. This is the reason for the type of series we got.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.